2022
DOI: 10.1093/ehjopen/oeac023
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of left atrial strain in patients with congenital aortic stenosis

Abstract: Aim To explore whether left atrial (LA) strain with speckle tracking echocardiography (STE) can contribute to prognostication in patients with congenital aortic stenosis (CAS). Methods In this prospective study, consecutive outpatients with stable CAS and healthy adults were enrolled between 2011-2015. LA function was analyzed with STE using Tomtec software. Associations between LA strain (LAS) measurements and primary compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The included studies reported PALS in patients with AS as summarized in 2. 15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] LA strain was significantly reduced in AS patients and a PALS <21% was an independent predictor of prognosis. 21 strain (PALS) was independently associated with the primary outcome and an optimal cut-off value of <19% showed the highest diagnostic performance.…”
Section: Pals In Patients With Asmentioning
confidence: 99%
“…The included studies reported PALS in patients with AS as summarized in 2. 15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] LA strain was significantly reduced in AS patients and a PALS <21% was an independent predictor of prognosis. 21 strain (PALS) was independently associated with the primary outcome and an optimal cut-off value of <19% showed the highest diagnostic performance.…”
Section: Pals In Patients With Asmentioning
confidence: 99%
“…LAS analysis was performed in accordance with the previous consensus document by European Society of Cardiology. [13] The de nitions of LA strain, strain rate and volume are summarized in Supplementary table 1. Normative ranges for LA-S [13], LV-GLS [14], LV-SRe [15], and RV-FWLS [16] were extracted from the studies conducted in the same hospital.…”
Section: Speckle Tracking Analysismentioning
confidence: 99%
“…A higher atrial pressure induces mechanical stress on the atrial wall, which generates fibroblast activation and atrial fibrosis [ 123 ] ( Figure 2 ). Left atrial dysfunction might appear before atrial enlargement and ventricular damage [ 124 , 125 ]. This could be an initial indicator of atrial cardiomyopathy and might reveal the presence of cardiac injury in aortic stenosis [ 124 , 125 ].…”
Section: Valvular Heart Disease and Atrial Cardiomyopathymentioning
confidence: 99%
“…Left atrial dysfunction might appear before atrial enlargement and ventricular damage [ 124 , 125 ]. This could be an initial indicator of atrial cardiomyopathy and might reveal the presence of cardiac injury in aortic stenosis [ 124 , 125 ]. Atrial remodeling in aortic stenosis can serve as a substrate for atrial fibrillation [ 126 , 127 ] ( Figure 1 ).…”
Section: Valvular Heart Disease and Atrial Cardiomyopathymentioning
confidence: 99%